Physical and Milling Quality of Milled Rice in Indonesia - Mahargono Kobarsih; Siti Dewi Indrasari (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2021)
More than 250 rice varieties are grown in Indonesia from new superior varieties and local varieties with aromatic, non-aromatic aromas and pigmented rice. Rice quality is one factor that must be considered in addition to high productivity. Generally, the quality of grain and rice quality in Indonesia have met the quality standards set based on SNI 0224-1987/SPI-TAN/01/01/1993 and SNI 6128:2020. Ricequality is determined by several factors such as grain appearance, nutritional value, cooking and eating quality and become one of the foremost considerations for rice buyers. Such information can be utilized as basic data of character of genetic resources on assembling of new superior varieties by rice breeders. Those information can be used as a descriptive information for farmers and rice productivity, high yield, and better rice quality. Good quality local cultivar can be used as parents for the formation of new superior varieties.